Assessment of a glutathione S-transferase and related proteins in the gill and digestive gland of Mytilus edulis (L.), as potential organic pollution biomarkers - Fitzpatrick, Patrick J.; O'Halloran, John; Sheehan, David; Walsh, Andrew R. (Biomarkers, 1997)
The response of the glutathione S-transferase (GST, EC 2.5.1.18) and related proteins of Mytilus edulis to environmental pollution load was assessed. Mussels were reciprocally transplanted between an industrial estuary (Douglas), a rural estuary (Youghal) and a m arine site (Bantry). In addition, m ussels were sam pled along a pollution gradient in an estuary receiving leather tannery effluent (Colligan). These latter m ussels were previously shown to be subject to oxidative stress resulting from the discharges. GST specific activity of cytosolic extracts from the gill and digestive gland tissues was determ ined for all anim als. Specific activity was shown to vary significantly in anim als from different sites, with highest specific activity always observed in sam ples (local and transplanted) taken from the industrial site. By com parison, the m ussels exposed to tannery discharges displayed no significant alteration in GST specific activity. Total intracellular glutathione (GSH) was also determ ined for sam ples taken from the Douglas and Youghal estuaries but no correlation with pollution load was observed. Using FPLC analysis, we observed no specific effect on the relative levels of the GST and the individual GST related proteins in gill or digestive gland sam ples from local or reciprocally transplanted anim als from Douglas or Youghal. The increase in GST specific activity observed in samples from the industrial estuary are indicative of a possible, specific inductive agent at this site. The results from the tannery site, by com parison, indicate that general oxidative stress does not result in elevated G ST specific activity in M. edulis.